Proceedings 24th Annual International Computer Software and Applications Conference. COMPSAC2000
DOI: 10.1109/cmpsac.2000.884778
|View full text |Cite
|
Sign up to set email alerts
|

An object-oriented Web test model for testing Web applications

Abstract: In recent years, Web applications have grown rapidly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 7 publications
0
67
0
1
Order By: Relevance
“…There already exist model-based approaches for testing of web applications, e.g., in [15,26], but they usually focus on the generation of test cases for functionality testing. Different studies have shown that stochastic models, in particular Markov chains, provide benefits for functionality testing [26,13,27].…”
Section: Related Workmentioning
confidence: 99%
“…There already exist model-based approaches for testing of web applications, e.g., in [15,26], but they usually focus on the generation of test cases for functionality testing. Different studies have shown that stochastic models, in particular Markov chains, provide benefits for functionality testing [26,13,27].…”
Section: Related Workmentioning
confidence: 99%
“…Using the links and forms it is possible to add, edit or delete data of the Web application by executing the test case script. There exists also a lot of works that have focused their research on functional testing based on a formal model such as [25,28,42]. We can also mention some Web application tools (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Kung et al [5] developed a test generation method for web testing to capture structural and behavioral test artifacts of web applications. The entities are represented as objects, and their structures, relationships and dynamic behaviors are described.…”
Section: Related Workmentioning
confidence: 99%